Pemberdayaan Masyarakat Melalui Kelompok Pengolah Dan Pemasar Ikan Minataruna: (Studi kasus di Padukuhan Kembang, Kalurahan Wonokerto, Turi, Sleman) - Wardani, Fera Arista (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Community empowerment is a program implemented by the community and for the community to provide certain power or abilities with the aim of improving the quality and welfare of the community so that it is better in all fields. This is what the Padukuhan Kembang women do through the Minataruna Fish Processing and Marketing Group. With the formation of the Minataruna Fish Processing and Marketing Group, it is hoped that it will be able to alleviate poverty, increase family income, and be able to develop the potential of existing resources to be independent, innovate and be creative in fish processing. The technique used by researchers is a qualitative approach. The results of this research provide an illustration that equality, participation, self-reliance and sustainability will produce an empowerment program that truly stands independently on its own two feet.